The roles of short-chain fatty acids derived from colonic bacteria fermentation of non-digestible carbohydrates and exogenous forms in ameliorating intestinal mucosal immunity of young ruminants - He, Zhiyuan; Dong, Hong (Frontiers in Immunology, 2023)
Short-chain fatty acids (SCFA) are a class of organic fatty acids that consist of of 1 to 6 carbons in length. They are primary end-products which arise from non-digestible carbohydrates (NDC) fermentation of colonic bacteria. They are the fundamental energy sources for post-weaning ruminants. SCFA represent the major carbon flux of diet through the gut microbiota to the host. They also play a vital role in regulating cell expansion and gene expression of the gastrointestinal tract (GIT). Recently, remarkable progresses have been made in understanding the immunomodulatory effects of SCFA and their interactions with the host. The processes involved in this study encompassed inflammasome activation, proliferation of lymphocytes , and maturation of intestinal mucosal immunity maturation. It is important to note that the establishment and maturation of intestinal mucosal immune system are intricately connected to the barrier function of intestinal epithelial cells (IEC) and the homeostasis of gut microbiota. Thus, insights into the role of SCFA in enteric mucosal immunoreaction of calves will enhance our understanding of their various regulatory functions. This review aims to analyze recent evidence on the role of SCFA as essential signaling molecules between gut microbiota and animal health. Additionally, we provide a summary of current literature on SCFA in intestinal mucosal immune responses of dairy calves.